Lymphaticovenular anastomosis for recurrent cellulitis in a dementia patient with lymphedema - Shuhei Yoshida, MD, PhD; Isao Koshima, MD, PhD; Hirofumi Imai, MD; Ayano Sasaki, MD; Shogo Nagamatsu, MD, PhD; Kazunori Yokota, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2020)
We describe a dementia patient with comorbid recurrent cellulitis and lymphedema in the left lower limb who was treated successfully for recurrent cellulitis by lymphaticovenular anastomosis (LVA). The patient, an 83-year-old woman, suffered from recurrent cellulitis three times a year on average for 15 years. Compression therapy was impossible because of dementia. After LVA, there has been no recurrence of cellulitis for 2 years.It is difficult to administer decongestive lymphatic therapy in some patients, such as patients with dementia. LVA is a promising treatment for recurrent cellulitis in a dementia patient with lymphedema.